KONSEP ADAB DALAM KITAB AKHLAAQU AHLI AL-QUR’AN DAN TIBYAN FI ADABI HAMALATI DENGAN TUJUAN PENDIDIKAN ISLAM - Haqi, Ahmad Abdul; Ghani, Ainal; Meriyati, Meriyati (STKIP Pesisir Selatan, 2024)
Memorizers of the Qur'an who ignore their etiquette will find it difficult to practice the contents of the Qur'an so that they become a bad example for others, there is a tendency for arrogance, arrogance and other less praiseworthy behavior, thus the trust and honor that a person will gain memorizing the Qur'an can be lost if they do not maintain their etiquette. This research includes using qualitative methods with library research. The research results obtained after studying, that every person who intends to focus on the Al-Quran must have the following etiquette, namely Cleaning the Mouth, Reading in a Pure Condition, Reading in a Clean Place, Facing the Qibla, Starting the Qiraah with Ta'awudz, Getting in the habit of starting each surah with basmalah, Mentadaburi Ayat, Repeating certain verses to reflect on, crying when reading the Koran, Reading with Tartil, Asking for Allah's Grace when Reading the Verse of Rahmat, Respecting the Koran, Not reading the Koran in a language other than Arabic, Reading Al-Qur'an Using Sabah Qiraah, Adab changing Qiraah Variations, Reading Al-Qur'an in the Order of Mushaf, Reading Al-Qur'an with Mushaf, Qiraah with Group, Reading Al-Qur'an in Turns, Raising Your Voice When Reading Al-Qur'an -Qur'an, Improving the Voice during Qiraah, Starting Qiraah from the Beginning Theme, Makruh Conditions for Reading the Qur'an, Prostrating recitations when encountering prayer prayer verses.